Determinants of Work Stress in Delivery Couriers in South Tangerang Area - Triana Srisantyorini; Munaya Fauziah; Andriyani Andriyani; Tria Astika Endah Permatasari; Irna Hasanah; Nurmalia Lusida; Ernyasih Ernyasih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Stress is a condition or situation where physical and emotional responses will arise when the ability and needs of workers do not match the job requirements. Statistical data shows that there are 440,000 cases in the UK, with 1,380 cases experiencing work-related stress. In Indonesia, especially in the capital city of DKI Jakarta, it is estimated that around 1.33 million of the 9.5 million population of DKI Jakarta are estimated to experience stress due to work. According to the Indonesian Ministry of Health in 2021, the impact and consequences of work stress will have an impact in the short and long term. The approach in this study uses a cross-sectional approach. This research was conducted at several shipping companies in South Tangerang. This research was conducted in July 2022. Based on the results of the study, it was found that sleep quality had a significant relationship between work stress and sleep quality (p=0.026); social support, there is no significant relationship between work stress and social support (p=0.572); work fatigue, there is a significant relationship between work stress and work fatigue (p=0.000); workload on work stress, found a significant relationship between work stress and workload (p=0.038); the variable that has the most significant influence on determining work stress scores is the work fatigue variable.